Hydrogen atom ionization in femtosecond laser field: Numerical solution of the TDSE using CWFDVR method - Ch.Aldarmaa; L.Khenmedekh; G.Zorigt (Scientific transaction of the National University of Mongolia. Physics, 2022)
We present an discrete variable representation for solving the time-dependent Schrodinger equation for an atomic system interacting with an intense laser pulse. Instead of the usual finite difference (FD) method, the radial coordinate is discretized using the discrete variable representation (DVR) constructed from Coulomb wave functions. Our results are in excellent agreement with other accurate theoretical calculations using different methods.